c-Jun Downregulation by HDAC3-Dependent Transcriptional Repression Promotes Osmotic Stress-Induced Cell Apoptosis - Xia, Yan (2007)
c-Jun, a major transcription factor in the activating protein 1 (AP-1) family of regulatory proteins, is activated by many physiologic and pathologic stimuli. However, whether c-jun is regulated by epigenetic modification of chromatin structure is not clear. We showed here that c-jun was transcriptionally repressed in response to osmotic stress via a truncated HDAC3 generated by caspase-7–dependent cleavage at aspartic acid 391. The activation of caspase-7, which is independent of cytochrome c release and activation of caspase-9 and caspase-12, depends on activation of caspase-8, which in turn requires MEK2 activity and secretion of FAS ligand. The cell apoptosis induced by the truncated HDAC3 or enhanced by c-Jun deficiency during osmotic stress was suppressed by exogenous expression of c-Jun, indicating that the downregulation of c-Jun by HDAC3-dependent transcriptional repression plays a role in regulating cell survival and apoptosis.